2003
DOI: 10.1093/molbev/msg102
|View full text |Cite
|
Sign up to set email alerts
|

Size Matters: Non-LTR Retrotransposable Elements and Ectopic Recombination in Drosophila

Abstract: The Drosophila melanogaster genome contains approximately 100 distinct families of transposable elements (TEs). In the euchromatic part of the genome, each family is present in a small number of copies (5-150 copies), with individual copies of TEs often present at very low frequencies in populations. This pattern is likely to reflect a balance between the inflow of TEs by transposition and the removal of TEs by natural selection. The nature of natural selection acting against TEs remains controversial. We prov… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

18
274
1

Year Published

2004
2004
2023
2023

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 212 publications
(297 citation statements)
references
References 67 publications
18
274
1
Order By: Relevance
“…Although these observations are also consistent with several alternative hypotheses (e.g. accumulation of deleterious insertions due to decreased selection efficiency within these regions) that do not necessitate ectopic recombination, there is increasing support from the drosophila model for significant selection against TE loci due to their potential for instability [5] Recent data from humans, showing stronger selection against full-length L1 elements than their truncated counterparts, is also highly suggestive of selection against ectopic recombination instability in our own lineage [6], particularly when taken together with an earlier genomic analysis of TE accumulation on human sex chromosomes which indicated that negative selection on L1s was related to L1 insertion size [7] as opposed to the full length vs. non-full length status of insertions. In the latter work, a statistically significant accumulation of >500bp but less-thanfull-length L1 inserts on the human sex chromosomes vs. the autosomes [7].…”
Section: Introductionsupporting
confidence: 79%
See 1 more Smart Citation
“…Although these observations are also consistent with several alternative hypotheses (e.g. accumulation of deleterious insertions due to decreased selection efficiency within these regions) that do not necessitate ectopic recombination, there is increasing support from the drosophila model for significant selection against TE loci due to their potential for instability [5] Recent data from humans, showing stronger selection against full-length L1 elements than their truncated counterparts, is also highly suggestive of selection against ectopic recombination instability in our own lineage [6], particularly when taken together with an earlier genomic analysis of TE accumulation on human sex chromosomes which indicated that negative selection on L1s was related to L1 insertion size [7] as opposed to the full length vs. non-full length status of insertions. In the latter work, a statistically significant accumulation of >500bp but less-thanfull-length L1 inserts on the human sex chromosomes vs. the autosomes [7].…”
Section: Introductionsupporting
confidence: 79%
“…Nevetheless, the full extent to which ongoing negative selection is occurring against both individual and groups of TE insertions due to their potential for ectopic recombination remains to be clarified. In support of the hypothesis that a significant historical selection pressure has existed against TE copy accumulation based on instability, several studies have demonstrated a tendency for TEs to accumulate in low recombining areas of the genome (discussed in [5]). Although these observations are also consistent with several alternative hypotheses (e.g.…”
Section: Introductionmentioning
confidence: 94%
“…Another important prediction of the ectopic exchange hypothesis for containment of TE copy number is that incomplete copies of the TEs are expected to be less likely to participate in ectopic exchange (Petrov et al 2003) and therefore these smaller members of the TE family will persist longer in the Figure 5. Ectopic exchange leading to a duplicated and deleted chromosome.…”
Section: The Ectopic Exchange Modelmentioning
confidence: 99%
“…Ectopic recombination (unequal recombination, that is, recombination between homologous elements located in nonhomologous positions) and TEs can cause large rearrangements. Ectopic recombination has been suggested to be the most important mechanism of genome size reduction and may provide a partial 'return ticket from genomic obesity' (Vicient et al, 1999;Petrov et al, 2003). The evidence that deletions are mediated by recombination is the presence of 'solo long terminal repeats (LTRs)' that remain in the genome after recombination between two LTRs deletes the internal regions (Vitte and Panaud, 2003).…”
Section: Processes Acting In Regions Of Reduced Recombinationmentioning
confidence: 99%